Sensitivity of the N. AEGEAN SEA ecosystem to Black Sea Water inputs - PETIHAKIS, G.; TSIARAS, K.; TRIANTAFYLLOU, G.; KALARONI, S.; POLLANI, A. (Mediterranean Marine Science, 2014)
The effect of Black Sea Water (BSW) inputs on the North Aegean Sea productivity and food web dynamics was investigated, by means of sensitivity simulations, investigating the effect of the inflowing BSW, in terms of inorganic nutrients and dissolved organic matter. The model used has been successfully applied in the area in the past and extensively presented. Considering the importance of the microbial loop in the ecosystem functioning, the role of the dissolved organics and in order to achieve a more realistic representation of the Dissolved Organic Matter pool, the bacteria sub-model was appropriately revised. The importance of the microbial loop is highlighted by the carbon fluxes where almost 50% of carbon is channelled within it. The impact of dissolved organic matter (DOM) (in the inflowing to the Aegean Sea, BSW) appears to be stronger than the impact of dissolved inorganic nutrients, showing a more extended effect over the N Aegean. Bacterial production and biomass is more strongly affected in the simulations by modified DOM, unlike phytoplankton biomass and production, which are more dependent on the inflowing nutrients and particularly phosphorus (inorganic and dissolved organic). In the phytoplankton composition, the dinoflagellates appear to be mostly affected, being favoured by higher nutrient availability at the expense of all other groups, particularly picoplankton, indicating a shift to a more classical food chain.